Penggunaan Aplikasi Dalam Talian Untuk Proses Pembelajaran dalam Kalangan Mahasiswa di Universiti Malaya: Isu dan Solusi: Utilization of Online Applications For Learning Process Among Students In The University of Malaya: Issues and Solutions - Kamarudin, Nurul Husnina; Ali @ Mat Zin, Aizan (Journal Al-Muqaddimah, 2024)
The national education system has undergone significant evolution in line with the country's development and capabilities. With technological advancements across various fields, the use of technology in education has also progressed over time. Technological progress is deemed essential to stay relevant within the education system. The e-learning approach, or online learning, has become a familiar method at the higher education level. Hence, this study focuses on the MAYA application, an online platform utilized by students at the University of Malaya (UM) for academic matters. The objective of this study is to assess the usage of the MAYA application in the learning process at UM, specifically addressing issues faced by students based on their experiences. Findings from the study have led to proposed solutions to enhance the performance and efficiency of the MAYA application. The research methodology employed in this study is a quantitative approach to obtain relevant data. The study outcomes provide a comprehensive insight into the utilization of MAYA at UM with the expectation that these proposed improvements will enhance students’ learning experiences and the university administrative efficiency in addressing future issues.